Informational behavior of parents of children with central auditory processing disorder (CAPD) - Condurú, Marise Teles (2019)
Study on the informational behavior of parents of children with Central auditory processing disorder (CAPD), in order to analyze their information needs on CAPD. Part of a bibliographical research and exploratory about informational behavior through the behavioral models proposed by scholars like Wilson and Choo, as well as on the auditory processing and the disorder that occurs and which compromises the learning and quality of life of children, young people and adults. The research data were collected in the Associação Beneficente Milton Pereira de Melo, through questionnaires to the participants and were assessed from a qualitative approach, seeking to understand the behavior of parents about information needs. The results indicate that the informational needs highlighted current and are still quite far from being fully resolved, even the parents having acquired knowledge about the CAPD, still remain many questions that need to be clarified so that they can ensure better quality of life to the children. It is concluded that the results of the survey were positive, since the topic is still little publicized in CAPD society, collaborating so that parents have less concern about the future of their children.